The Role of Pesantren Culture in Developing Academic Character: A Study on the Positive Impact of the Cultural Environment at Pesantren Luhur Sabilussalam - Nashihin, Muhammad Ihsan; Majeed, Muhammad Kashif; Derysmono, Derysmono; Armadi, Ari; Syukur, Agus (UIN Syarif Hidayatullah Jakarta, 2025)
This study aims to investigate the impact of pesantren culture on students' academic achievements in higher education. A pesantren is a traditional Islamic boarding school comprising key elements such as a kyai (religious leader), santri (students), dormitories, and a mosque. This research explores how its cultural practices influence student outcomes by focusing on one type of pesantren that operates in the evening, exemplified by Pesantren Luhur Sabilussalam. The study employs an analytical survey design with a cross-sectional approach and uses quantitative data collection and analysis methods. Findings indicate that four core cultural components- Islamic study sessions (pengajian), religious activities, the pesantren environment, and interpersonal relationships- contribute positively to students' academic and non-academic success, accounting for a 45% impact on their performance in higher education